2011
DOI: 10.1111/j.1750-2659.2011.00290.x
|View full text |Cite
|
Sign up to set email alerts
|

Influenza vaccination in patients with pulmonary sarcoidosis: efficacy and safety

Abstract: Please cite this paper as: Tavana et al. (2011) Influenza vaccination in patients with pulmonary sarcoidosis: efficacy and safety. Influenza and Other Respiratory Viruses DOI: 10.1111/j.1750‐2659.2011.00290.x. Background  Sarcoidosis is an inflammatory, granulomatous disorder of unknown etiology. The role of cellular and humoral immune systems in this disease is unclear, whereas dysregulation of the immune system is suggested. Patients with sarcoidosis show diverse responses while exposed to various antigens. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 31 publications
(74 reference statements)
0
10
0
Order By: Relevance
“…Strategies to circumvent detrimental toxicities of both corticosteroids and alternative immunosuppression are important to incorporate into the multidisciplinary management of patients. For example, maintaining routine recommended vaccinations for infections such as influenza or pneumococcus should be considered (136,137). Additionally, bone health should be addressed upon initiation of corticosteroids and regularly thereafter; clinical risk assessment (yearly) and intermittent bone mineral density testing can be incorporated based on duration of corticosteroid use, age, and risk scores (138).…”
Section: Treatment-associated Issuesmentioning
confidence: 99%
“…Strategies to circumvent detrimental toxicities of both corticosteroids and alternative immunosuppression are important to incorporate into the multidisciplinary management of patients. For example, maintaining routine recommended vaccinations for infections such as influenza or pneumococcus should be considered (136,137). Additionally, bone health should be addressed upon initiation of corticosteroids and regularly thereafter; clinical risk assessment (yearly) and intermittent bone mineral density testing can be incorporated based on duration of corticosteroid use, age, and risk scores (138).…”
Section: Treatment-associated Issuesmentioning
confidence: 99%
“…91,92 Similarly, lower serum ACE levels in patients with pulmonary sarcoidosis associated with a more vigorous immunogenic response to influenza vaccination. 93 However, not all human cohorts confirm this inverse association, 94,95 and such observational gene association studies must be interpreted with caution.…”
Section: Immunologic Effects Of Ras Manipulation In Humansmentioning
confidence: 99%
“…Particularly important in sarcoidosis is concern for disease flare after vaccination. It is reassuring that a prior study of influenza vaccination in a small sample of sarcoidosis patients did not note any disease flare-up immediately after vaccination as well as during a 6 month follow-up period (17). However, close followup of sarcoidosis patients will be vital to observe if vaccination against COVID-19 may potentially precipitate a disease flare.…”
Section: Challenges Of Covid-19 Vaccination In Sarcoidosismentioning
confidence: 93%
“…Conversely, Tavana and colleagues performed a prospective study comparing 23 sarcoidosis patients to 26 healthy controls and measured serologic response to influenza vaccination. They found that the serologic response to multiple influenza antigens (H1N1, H3N2, and B) was comparable between both groups (17). However, both studies failed to clarify if patients in the sarcoid cohorts were receiving immunosuppressive medications.…”
Section: Vaccinations In Sarcoidosismentioning
confidence: 99%